Common mental disorders in young adults: temporal trends in primary care episodes and self-reported symptoms - Judi Kidger; James B Kirkbride; Kate Walters; Shamini Gnani; Francesca Solmi; David P J Osborn; Jennifer Dykxhoorn; Antonio Lazzarino (BMJ Mental Health)
Background Rates of common mental disorders (CMDs) including anxiety, depression and stress, treated in primary care have increased among young adults, but it is unclear if this reflects more help-seeking and/or an increase in symptoms, and if there are differences across sociodemographic groups.Objective This study examined trends in primary care-recorded CMD and self-reported psychological distress symptoms in young adults over time.Methods We used data from participants born between 1980 and 2003 in two datasets: UK primary care records and longitudinal cohort data. Participants were followed from age 16 to age 39 (maximum) or the end of the follow-up (2019–2020). Annual incidence rates of recorded CMD overall and by sociodemographic group were calculated for 2009–2019, using incidence rate ratios to explore changes. We calculated annual self-reported psychological distress symptoms from cohort data, calculating ratios to explore changes over time.Findings Between 2009 and 2019, recorded CMD increased by 9.90%, while average psychological distress symptoms rose by 19.33%. The sharpest increases for both recorded CMD and average psychological distress symptoms were observed in older adolescents (ages 16–19) and those born after 1995. Recorded CMD increased more in males (20.61%) than in females (7.65%), despite similar symptom increases. Recorded CMD increased the most in the least deprived areas (16.34%) compared with the most deprived areas (3.55%), despite comparable rises in psychological distress symptoms.Conclusions Both recorded CMD and psychological distress symptoms in young adults increased between 2009 and 2019, which may indicate that the rising primary care-recorded CMD reflects increased symptom burden.Implications Differences between recorded CMD and psychological distress symptoms across sociodemographic groups highlight potential misalignment in mental healthcare with underlying population need, indicating that the most affected groups may not be those receiving the most care.